IMPLEMENTASI ASSEMEN DIAGNOSTIC UNTUK MENENTUKAN PROFIL GAYA BELAJAR SISWA DALAM PEMBELAJARAN DIFERENSIASI DI SEKOLAH DASAR - Yani, Dwi; Muhanal, Susriyati; Mashfufah, Aynin (Jurnal Inovasi dan Teknologi Pendidikan, 2023)
The profile of a Pancasila student is a student character that must be formed and realized in the implementation of the independent curriculum. Learning that meets students' learning needs in accordance with the profile of students' learning styles characterizes the implementation of the independent curriculum. This study aims to determine the implementation of diagnostic assessments to determine student learning style profiles in differentiated learning in elementary schools. This research is a qualitative research using observation, documentation and interview data collection techniques. The results showed that the diagnostic assessment to determine students' learning style profiles had a good effect on differentiated learning in thematic learning in elementary schools through process differentiation, content differentiation and product differentiation which were in accordance with the principles of differentiation learning. Diagnostic tests or pre-learning tests are related to mapping students' learning styles, interests, and prior knowledge so that teachers can carry out differentiated learning according to students' needs. Optimization of diagnostic tests is carried out in order to improve the quality of thematic learning so that it fits the needs of students and the time used in learning is also effective